Molecular arrangement between electrolyte and alcohol at the air/water interface - Gao, G.; Nguyen, C.; Phan, Chi (Elsevier, 2017)
© 2017 Elsevier B.V. While it is conventionally believed that interaction between electrolytes and surfactants at the air/water interface can have profound impact on surface tension, a quantitative description remains elusive. In this study, the surface arrangement of MIBC at 1 M and 2 M NaCl solution was investigated by molecular dynamics. The main aim of simulation was to explore the molecular arrangement and explain the synergistic effect, which was evidenced by existing experimental data. The simulation was able to confirm experimental results as well as the underlying molecular arrangement. Specifically, it was found that Na + and Cl - has an opposite effects on surface tension. The net effect of Na + /Cl - on surface tension is determined by the relative ratio between the two ions near the interface. This relative ratio, in turn, depends on MIBC concentration. As a result, NaCl decrease tension at low MIBC and increase tension at high MIBC. The mechanism should be the same governing principle for other surfactant/electrolyte mixture. The findings lay an important foundation for mixed surfactant/electrolyte systems.